STEMMING QUACKERY ON CONSTRUCTION SITES IN ABUJA-NIGERIA: SUPERVISION AND PRODUCTIVITY NEXUS - Richard JIMOH; Suleiman SULEIMAN; Rasheed ISA; Luqman OYEWOBI (Journal of Construction Project Management and Innovation)
Productivity being a major concern to production and operation managers, higher productivity can be achieved through better utilization of available resources. Effective supervision of construction workers is one of the processes through which high productivity can be achieved. Hence, a combination of methods were used to compare the productivity and level of adherence to quality on 20 active construction sites through the use of direct measurement of productivity, personal un-obstructive observations and 10 structured interviews among construction professionals in Abuja-Nigeria. Findings showed that there was no difference between the sites supervised by professionals and non-professionals in terms of labour productivity. In a related development, here was also no difference in terms of adherence to quality between the sites supervised by professionals and non-professionals except in blocklaying due to the perceived “proficiency” by the non-professionals (masons as foremen). Quackery may continue to plague the Nigerian construction industry if clients held belief is not changed and construction foremen are not trained to meet up with the demands of the industry. Non-professionals such as foremen should be trained and certificated by Council of Registered Builders of Nigeria (CORBON) in order to improve supervision and by extension productivity on construction sites.